Sistem Optimasi Inventory Berbasis Layanan Web Di PT Pelita Biru - Bakti, Cristeddy Asa (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
Various types of LPG sold, requiring a precise inventory management, especially the facts on the ground are often encountered uncertainties include uncertainty of demand and the performance cycle. The aim of this research is to develop decision making system to optimize inventory by the Economic Order Quantity method based on the Bowersox formula by using the combining of variables for demand uncertainty and performance cycle. The system uses the web service media method for easy access and maintenance with centralized data on the server and users only use the existing browser. The method of categorizing goods uses the category ABC by dividing the type of goods into categories A (very important), B (important) and C (not important). The results provide safe inventory value calculations based on variables of uncertainty and performance cycles. With the optimization resulting from this system, the company can maintain the availability of the goods by making appropriate arrangements, priorities, and the amount so as to minimize the occurrence of the possibility of excess and lack of stock.